An updated review on the link between oral infections and atherosclerotic cardiovascular disease with focus on phenomics - Bezamat, Mariana (Frontiers in Physiology, 2022)
Atherosclerotic cardiovascular diseases (ACVD) and oral infections such as periodontal disease, dental caries, and apical periodontitis are diseases that affect a great portion of the worldwide population. Both are complex in nature and several studies show that they share etiological factors but a causal relationship between them has not been yet established due to the lack of well-designed clinical trials. Many studies in the recent years show convincing evidence of different mechanisms that might be involved in this association including chronic inflammation and immune response. However, some of these mechanisms are controversial because of confounding factors. It has been suggested that maladaptive inflammatory reactivity, determined in part by single nucleotide polymorphisms (SNPs) in pathway genes, could influence the association between oral infections and cardiovascular diseases as pleiotropic genes. That is, these conditions could be outcomes of similar inflammatory pathways. Phenomics, the study of the changes in phenotypes or traits considering environmental variables and genetics is efficient in assessing and determining pleiotropic genes. Future research should focus on analyzing a combination of oral inflammatory conditions instead of focusing on one inflammatory phenotype alone and consider pleiotropy as a mechanistic contributor for these associations. Further, prospective observational studies seeking to follow the development of oral disease and subclinical ACVD will foster the understanding of the impact of oral health on general systemic health. Lastly, to demonstrate that oral infections would increase risk for subclinical ACVD development, clinical trials proposing to treat those infections considering genetic background and all other confounders are needed.